The immediate pain relief of low-level laser therapy for burning mouth syndrome: a retrospective study of 94 cases - Mu, Wenxin; Li, Shanshan; Lu, Qian; Wang, Juan; Tao, Xiaoan (Frontiers in Oral Health, 2024)
SignificanceBurning mouth syndrome (BMS) is a chronic orofacial pain disorder that seriously affects quality of life of patients. In recent years, Low-level laser therapy (LLLT) has been regarded as an important innovation in pain management, but there is insufficient evidence of its effectiveness in patients with painful BMS. This study aimed to evaluate the efficacy of LLLT for immediate pain relief due to BMS.MethodsThis retrospective study included 94 BMS patients that were treated with an intraoral semiconductor laser (635 nm, 100 mW/cm2). Pain was self-assessed before and immediately after LLLT sessions using a 0-to-10 visual analogue scale (VAS). Paired-samples t-test and multivariable binary logistic regression were used to analyze overall efficacy and its influencing factors.ResultsAfter standardized LLLT session, 71.3% of patients reported an immediate pain decrease. Compared to pre-LLLT treatment, the VAS immediately post-LLLT was significantly reduced (P < 0.001). Mean post-LLLT VAS reduction was 2.2 ± 2.0, equivalent to 39.9% of the initial pain level. Meanwhile, low VAS before treatment, history of smoking or alcohol, xerostomia, and gingival lesions correlated with worse LLLT efficacy. There were no side effects or adverse reactions were noticed by the practitioner or reported by the patients.ConclusionsLLLT may provide non-pharmacological, non-invasive, side-effect-free, and rapid pain relief for painful BMS patients. No baseline characteristics affecting overall efficiency were found except for VAS before treatment, history of smoking or alcohol, xerostomia, and gingival lesions.